Serum neopterin and ischemia modified albumin levels are associated with the disease activity of adult immunoglobulin A vasculitis (Henoch‐Schönlein purpura). (14th August 2019) - Omma, Ahmet; Colak, Seda; Can Sandikci, Sevinc; Yucel, Cigdem; Erden, Abdulsamet; Sertoglu, Erdim; Ozgurtas, Taner
Abstract: Aim: The aims of the study are to investigate serum neopterin and ischemia modified albumin (IMA) levels in patients with immunoglobulin A vasculitis (IgAV) and evaluate the association of these markers with disease activity and relapse. Method: Thirty‐four consecutive adult patients (24 male and 10 female) admitted to the rheumatology clinic and met the IgAV American College of Rheumatology (ACR) criteria were enrolled in this cross‐sectional study. Demographic and clinical features of IgAV and a control group were recorded into a predefined protocol. Disease activity was categorized as "remission" or "active" according to Birmingham Vasculitis Activity Score (BVAS). BVAS ≥ 1 was accepted as "active". Serum neopterin levels, high‐sensitivity C‐reactive protein (hsCRP) and IMA were evaluated according to BVAS and compared to the healthy control group. Results: Serum median (interquartile range) neopterin, IMA levels and hsCRP were higher in the study group than in control group (2.01 [12.5] ng/mL vs 1.77 [1.37] ng/mL, 0.67 [0.2] ng/mL vs. 0.43 [0.17] ng/mL, 5.6 [17.1] mg/L vs. 1.55 [1.6] mg/L, P  = .095, P  < .001 and P  = .002, respectively). When evaluated according to BVAS, IMA and hsCRP levels were significantly higher in the group with active disease (0.77 [0.12] vs 0.61 [0.13] and 14.85 [4.6], P  = .009 and P  = .03, respectively). Serum neopterin levels were significantly higher in the active group compared to BVAS (18.95 [32.36] vs 1.63 [1.48], P  < .001). Conclusion: Oxidative stress is important in IgAV pathogenesis. Roles of hsCRP, neopterin and IMA as potential markers of diagnosis and disease activity seem to be worth studying in future studies with larger study groups.